Konsep Sangkan Paraning Dumadi dalam Syiir Sun Ngawiti Karya Kiai Sa'dullah Majdi - Wahyu Budiantoro (LPPM UIN Saizu Purwokerto, 2021)
The concept of sangkan paraning dumadi is always related to monotheism. In the Javanesetradition, the concept is inherent in every tradition and local wisdom, so that each individualis able to appreciate the origins of the creation of his life. One form of local wisdom is the useof syiir as a symbol. In this study, the syir that was spoken was sun ngawiti by Kiai Sa’dullahMajdi. The purpose of this study is to identify and explain the concept of sangkan paraningdumadi in the syiir. The data was obtained documentatively through a search of a numberof articles related to the syiir and the concept of sangkan paraning dumadi. It is used to findout the theoretical/epistemological concept of poetry and the study of sangkan paraningdumadi. The results of this study indicate that syiir sun ngawiti has the concept of sangkanparaning dumadi in the form of monotheism, accentuatio of manifestation as a servant, andcharity and faith in knowledge